Theory of solid-propellant nonsteady combustion - Novozhilov, Boris V.; Novozhilov, Vasily B. (Wiley-ASME press series, 2021)
"Despite significant developments and widespread theoretical and practical interest in the area of Solid-Propellant Nonsteady Combustion for the last fifty years, a comprehensive and authoritative text on the subject has not been available. Theory of Solid-Propellant Nonsteady Combustion fills this gap by summarizing theoretical approaches to the problem within the framework of the Zeldovich-Novozhilov (ZN- ) theory. This book contains equations governing unsteady combustion and applies them systematically to a wide range of problems of practical interest. Theory conclusions are validated, as much as possible, against available experimental data. Theory of Solid-Propellant Nonsteady Combustion provides an accurate up-to-date account and perspectives on the subject and is also accompanied by a website hosting solutions to problems in the book."--